Determination of Desorption Isotherms of Potato Using Gravimetric Method and Fast Isotherm Method. Issue 6 (11th April 2020) - Singh, Punit; Talukdar, Prabal
Abstract: The desorption isotherms of potato ( Solanum tuberosum ) were determined for a range of temperature 30–60 °C using gravimetric and fast isotherm method over the range of relative humidity 5–85%. The objective of this work is to investigate and document the best practice to perform experiments using both these two methods. The desorption isotherms obtained from the gravimetric method were fitted using three models: GAB, BET, and Oswin. A nonlinear least-square regression analysis was used to evaluate the constants of the three isotherm models. The goodness of the fit was determined by two statistical parameters: standard error and correlation coefficient. GAB model was found to be competent to describe desorption isotherms of potato followed by BET and Oswin model. Also, the sorption behavior of potato obtained from the fast isotherm method was validated to the standard gravimetric method.